Measurement of Antioxidant Activity toward Superoxide in Natural Waters - King, D. Whitney; Berger, Emma; Helm, Zachary; Irish, Eleanor; Mopper, Kenneth (Frontiers in Marine Science, 2016)
Antioxidants are a class of molecules that provide a protective function against reactive oxygen species (ROS) in biological systems by out competing physiologically important molecules for ROS oxidation. In natural waters, the reactivity of antioxidants gives an estimate of oxidative stress and may determine the reactivity and distribution of reactive oxidants. We present an analytical method to measure antioxidant activity in natural waters through the competition between ascorbic acid, an antioxidant, and MCLA, a chemiluminescent probe for superoxide. A numerical kinetic model of the analytical method has been developed to optimize analytical performance. Measurements of antioxidant concentrations in pure and seawater are possible with detection limits below 0.1 nM. Surface seawater samples collected at solar noon contained over 0.4 nM of antioxidants and exhibited first-order decay with a half-life of 3-7 minutes, consistent with a reactive species capable of scavenging photochemically produced superoxide.